A method for preparing a polymer film, a polymer film and its application
By preparing a polymer film with two-dimensional layered channels with transmembrane orientation, the problem that existing separation membrane materials are difficult to take into account both selectivity and passability, and the membrane separation effect with high selectivity and high passability is achieved.
Patent Information
- Application Number
- CN202411435238.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-15
- Publication Date
- 2025-02-11
- Estimated Expiration
- 2044-10-15
AI Technical Summary
It is difficult for existing separation membrane materials to take into account the high size uniformity and low torsion of mass transfer channels, resulting in a bottleneck effect that cannot be obtained both selectivity and passability in membrane separation technology.
A two-dimensional layered liquid crystal system was prepared by mixing amphiphilic liquid crystals with polar solvents, and combined with the addition of initiators, a polymer film with two-dimensional layered channels with transmembrane orientation was prepared. This method controls the channel size by controlling the content of polar solvents, and achieves continuous adjustment of nano- or sub-nanometer scales.
It has achieved high selectivity and high passivity of polymer films, breaking through the bottleneck that cannot be obtained both selectivity and flux of traditional film making processes, and has high application value in the field of membrane separation.
Smart Images

Figure CN118955799B_ABST
Abstract
Description
Technical Field
[0001] The present application relates to the field of membrane separation technology, and in particular to a method for preparing a polymer membrane, a polymer membrane and applications thereof, and further to a method for preparing a polymer membrane with controllable interlayer channels, a polymer membrane and applications thereof. Background Art
[0002] Membrane science and membrane technology are key basic technologies that affect the development of industries such as chemical industry, environment, medicine, and energy. Among them, membrane separation is the most widely used field of membrane science. In particular, separation membranes with nanopore size are core technologies in many fields such as seawater desalination, lithium-magnesium separation, carbon dioxide capture, osmotic pressure power generation, and fuel cells. The essence of membrane separation technology is to control the selective mass transfer behavior in the membrane. "Selectivity" and "permeability" are two core indicators for measuring the performance of membrane separation technology. At present, the mass transfer channels constructed by traditional membrane manufacturing processes have high tortuosity and low size uniformity, resulting in low permeability or / and low selectivity. The high-size uniformity two-dimensional sub-nano channels constructed by stacking two-dimensional material sheets have achieved high-selectivity membrane separation. However, the Z-shaped sub-nano channels formed by them significantly increase the mass transfer path and channel tortuosity, resulting in low permeability. An ideal selective mass transfer membrane should have both high selectivity and high permeability. The existing separation membrane material design ideas cannot take into account the "high size uniformity" and "low tortuosity" of the mass transfer channel, and thus cannot solve the bottleneck effect of the "selectivity" and "permeability" of membrane separation technology. Summary of the invention
[0003] The present application aims to solve at least one of the technical problems existing in the prior art. To this end, the present application proposes a preparation method of a polymer film, a polymer film and an application thereof.
[0004] In a first aspect of the present application, a method for preparing a polymer film is provided, comprising the following steps:
[0005] S1. preparing a two-dimensional lamellar liquid crystal system by mixing an amphiphilic liquid crystal with a polar solvent; the content of the polar solvent in the two-dimensional lamellar liquid crystal system is 1 wt% to 80 wt%;
[0006] S2, mixing an additive including an initiator with the two-dimensional lamellar liquid crystal system to prepare a precursor slurry;
[0007] S3, coating the precursor slurry on the surface of the substrate and performing an orientation treatment to obtain a wet film; the orientation direction of the orientation treatment intersects with the surface normal direction of the wet film;
[0008] S4, performing in-situ polymerization curing and drying treatment on the wet film.
[0009] According to the preparation method of the polymer film of the embodiment of the present application, at least the following beneficial effects are achieved: the method prepares the polymer film by multi-step coupling, specifically, firstly, a two-dimensional lamellar liquid crystal system containing a specific amount of polar solvent is prepared by mixing amphiphilic liquid crystal and polar solvent, wherein the effective volume of the amphiphilic liquid crystal small molecules changes under the conditions of self-interaction (van der Waals force, hydrogen bond, π bond, etc.) and the addition of polar solvent, and molecular self-assembly behavior occurs, resulting in lamellar microphase separation to form a lamellar structure, that is, a bilayer structure of lamellar lyotropic liquid crystal is formed, and a two-dimensional lamellar liquid crystal system with a local domain structure is obtained, and the polar solvent is filled between adjacent bilayers in the domain structure to form a two-dimensional solvated lamellar channel, and within the specific polar solvent content range, the phase The thickness of the solvent layer between adjacent bilayers will change with the content of polar solvent. The greater the content of polar solvent, the thicker the solvent layer and the larger the size of the two-dimensional solvated lamellar channel. The size of the interlayer two-dimensional solvated lamellar channel can be controlled by controlling the content (or addition amount) of polar solvent, thereby realizing precise and continuous control of the channel at the nanometer or sub-nanometer scale. By introducing additives including initiators into the two-dimensional lamellar liquid crystal system, a precursor slurry in a polymerizable state is obtained. The precursor slurry is then coated on the surface of the substrate, and an orientation treatment is performed in which the orientation direction intersects with the surface normal direction of the wet film to achieve alignment of domains and trans-membrane orientation of the two-dimensional solvent lamellar channel. The wet film is then subjected to in-situ polymerization curing and drying treatment to solidify the film structure. The polymer membrane prepared by the above method has several two-dimensional lamellar channels oriented across the membrane, and the channel arrangement and size are uniform. The method can control the size of the two-dimensional channels between layers by controlling the amount of polar solvent added within a specific range (or controlling the polar solvent content in the two-dimensional lamellar liquid crystal system), so as to achieve uniform and controllable channel size between membrane layers and continuous adjustable size at the nanometer or sub-nanometer scale. The prepared polymer membrane has both high selectivity and high permeability, thus breaking through the bottleneck that traditional membrane preparation processes cannot achieve both ion selectivity and flux. It has extremely high application value in the field of membrane separation (such as ion nanofiltration, ion transport, water treatment and other energy and environmental fields). Specifically, according to the separation requirements, the size of the channels between polymer membrane layers can be accurately controlled by the above method to meet the membrane separation size requirements.
[0010] In step S1, the amphiphilic liquid crystal has a hydrophilic end and a hydrophobic end, and the amphiphilic liquid crystal is generally a lyotropic liquid crystal. The amphiphilic liquid crystal may be a single component liquid crystal or a mixed component liquid crystal. Specific optional amphiphilic liquid crystal materials include but are not limited to Figure 1 The amphiphilic liquid crystal shown, Figure 1 In the groups A and A' of the amphiphilic liquid crystal shown, n>8; R1 involved in the group D' is selected from alkylene; and the shadows on the groups A, A', B, C, and D' indicate the connection positions between the groups.
[0011] The polar solvent may be a hydrogen bond donor solvent or a non-hydrogen bond donor solvent, specifically including but not limited to: water, methanol, ethanol, propanol, butanol, ethylene glycol, ethyl acetate, dichloromethane, chloroform, tetrahydrofuran, acetonitrile, acetic acid, acetone, hydrochloric acid, sulfuric acid, phosphoric acid, nitric acid, dimethylformamide, dimethyl sulfoxide.
[0012] In some embodiments of the present application, the content of polar solvent in the two-dimensional lamellar liquid crystal system is 1 wt% to 50 wt%, 20 wt% to 50 wt% or 40 wt% to 50 wt%. Accordingly, the dosage ratio of amphiphilic liquid crystal and polar solvent can be controlled as follows: 50 wt% to 99 wt% amphiphilic liquid crystal and 1 wt% to 50 wt% polar solvent; or 50 wt% to 80 wt% amphiphilic liquid crystal and 20 wt% to 50 wt% polar solvent; or 50 wt% to 60 wt% amphiphilic liquid crystal and 40 wt% to 50 wt% polar solvent.
[0013] In step S1, after the amphiphilic liquid crystal and the polar solvent are mixed, the liquid crystal molecules form a two-dimensional layered liquid crystal system through self-assembly.
[0014] In some embodiments of the present application, in step S1, the mixing method of the amphiphilic liquid crystal and the polar solvent is selected from at least one of a stirring ultrasonic method, a freeze-thaw cycle method, and a rotary evaporation method.
[0015] Among them, the ultrasonic stirring method can specifically include: after mixing the amphiphilic liquid crystal and the polar solvent, first stir to make the solid and liquid phases preliminarily mixed evenly, and then perform ultrasonic vibration to fully dissolve the undissolved materials in the system; and then repeat the above stirring and ultrasonic vibration steps twice or more. In addition, centrifugation and static treatment can be further performed in sequence, wherein the bubbles in the system are removed by centrifugation; during the static treatment process, the centrifuge tube mouth can be sealed with a sealing film to prevent solvent volatilization and impurities from mixing, and the liquid crystal molecules are allowed to stand to achieve full and uniform self-assembly, while eliminating the residual stress generated between domains during the stirring and mixing process. In the ultrasonic stirring method, the time of ultrasonic vibration can be controlled at 10min to 30min; the centrifugal speed can be controlled at 2000 r / min to 20000 r / min; the centrifugal time can be controlled to be ≥3 days.
[0016] The freeze-thaw cycle method may specifically include: after mixing the amphiphilic liquid crystal and the polar solvent, first freeze them until solidified, then thaw and stir them evenly; then repeat the above freezing, thawing and stirring steps twice or more. In addition, centrifugation and static treatment can be further performed in sequence, wherein centrifugation is used to remove bubbles generated by stirring in the system; during the static treatment process, a sealing film can be used to seal the centrifuge tube mouth to prevent solvent volatilization and impurities from mixing, and the liquid crystal molecules can be fully and uniformly self-assembled, while eliminating the residual stress generated between domains during the stirring and mixing process. During the above freeze-thaw cycle treatment process, the freezing temperature can be controlled to ≤-5°C; the thawing temperature can be controlled to 18°C to 25°C. The centrifugal speed can be controlled to 2000 r / min~20000 r / min; the centrifugal time can be controlled to ≥3 days.
[0017] The rotary evaporation method may specifically include: mixing the amphiphilic liquid crystal and polar solvent into a rotary evaporator, rotating at a low speed and heating to a suitable temperature to partially evaporate the solvent; when the solution is concentrated to a certain extent, stop heating, cool to room temperature, and stir the mixture with a thin glass rod; and repeat the above two steps twice or more. In addition, centrifugation and static treatment can be further performed in sequence, wherein centrifugation is performed to remove bubbles generated by stirring in the system; during the static treatment process, a sealing film can be used to seal the centrifuge tube mouth to prevent solvent volatilization and impurities from mixing, and the liquid crystal molecules can be fully and uniformly self-assembled, while eliminating the residual stress generated between domains during the stirring and mixing process of the sample.
[0018] In the rotary evaporation process, the rotation speed of the rotary evaporator can be controlled to be ≤1500r / min; the heating temperature can be controlled to be ≥60°C. The centrifugal speed can be controlled to be between 2000 r / min and 20000 r / min; and the centrifugal time can be controlled to be ≥3 days.
[0019] As described above, in step S1, the amount of polar solvent added or the content of polar solvent in the two-dimensional lamellar liquid crystal system can be adjusted within a specific range to control the size of the two-dimensional solvated lamellar channels in the two-dimensional lamellar liquid crystal system.
[0020] In some embodiments of the present application, in step S2, the mass ratio of the additive to the two-dimensional lamellar liquid crystal system is 1: (1-100000). Further, the mass ratio of the additive to the two-dimensional lamellar liquid crystal system may be 1: (2-10000), 1: (4-1000), 1: (5-100), 1: (8-50), 1: (10-30) or 1: (12-20).
[0021] In some embodiments of the present application, the viscosity of the precursor slurry is 1×10 3 mPa·s~1×10 9 mPa·s.
[0022] In some embodiments of the present application, the two-dimensional lamellar liquid crystal system and the amphiphilic liquid crystal in the precursor slurry form a focal conic texture, that is, the polarized microtexture characteristics of the two-dimensional lamellar liquid crystal system and the formulated precursor slurry are uniform "focal conic" characteristic textures.
[0023] In some embodiments of the present application, the initiator is a photoinitiator or a thermal initiator. The photoinitiator can be one or more of a free radical photoinitiator, a cationic photoinitiator, and a dual photoinitiator, wherein the dual photoinitiator is a photoinitiator having both free radical properties and cationic properties.
[0024] In some embodiments of the present application, the additive includes 0-99wt% functional monomer, 0-99wt% cross-linking agent, 1-100wt% photoinitiator, 0-99wt% thermal inhibitor; or, the additive includes 0-99wt% cross-linking agent, 1-100wt% photoinitiator, 0-99wt% thermal inhibitor; or, the additive includes 0-99wt% cross-linking agent, 1-100wt% photoinitiator, 0-99wt% thermal inhibitor. Among them, the cross-linking agent can be a water-soluble cross-linking agent, a fat-soluble cross-linking agent or others; specifically, one or more of epoxy cross-linking agents, amine cross-linking agents, isocyanate cross-linking agents, and olefin cross-linking agents can be used; the functional monomer can specifically be at least one of vinyl sulfonic acid, sodium vinyl sulfonate, and acrylamide.
[0025] In some embodiments of the present application, in step S2, the additive is first placed in an organic solvent for blending treatment, and then the organic solvent is removed, and then mixed with the two-dimensional lamellar liquid crystal system to prepare a precursor slurry. Among them, the organic solvent can be one or more of alcohols, ketones, esters, ethers, glycol derivatives, halogenated hydrocarbons, and aliphatic hydrocarbons. The blending process can be assisted by stirring, and the stirring time can be controlled to be ≥1 h; the method for removing the organic solvent can be negative pressure rotary evaporation; the negative pressure rotary evaporation method can be specifically carried out in a negative pressure vacuum environment (P≤0.1 bar) and at a temperature of ≥25°C; the processing time can be controlled to be ≥48 h. The above uniform blending of additives is achieved through organic solvents, combined with the amount control of polar solvents in the two-dimensional lamellar liquid crystal system, to ensure the low viscosity and polymerizability of the prepared precursor slurry.
[0026] In some embodiments of the present application, in step S2, the mixing of the additive with the two-dimensional layered liquid crystal system includes: first stirring and mixing, and then ultrasonically oscillating; and then repeating the stirring and mixing and ultrasonically oscillating for more than two times. Specifically, a stirring rod can be used for stirring and mixing, and the stirring rod can be an inert metal stirring rod; each ultrasonic oscillation time can be controlled to be ≥45 min. During the mixing process, the original layered structure in the two-dimensional layered liquid crystal system moves with the stirring in units of domains, and gradually absorbs the additive into the layered structure.
[0027] The mixing process of the above additives and the two-dimensional lamellar liquid crystal system can be further centrifuged and left to stand in sequence after the last stirring and ultrasonic oscillation treatment, wherein the centrifugation is used to remove the large bubbles generated by the stirring in the system; during the standing treatment, the centrifuge tube mouth can be sealed with a sealing film and left to stand to eliminate residual stress. The centrifuge speed can be controlled at 3500 r / min to 6000 r / min, the centrifuge time is ≥5 min, and the standing treatment time can be controlled to be ≥3 days.
[0028] In some embodiments of the present application, in step S3, the angle between the orientation direction of the orientation treatment and the surface of the wet film is 0° to 45°; and / or, the orientation treatment is oriented by mechanical friction during the coating process.
[0029] Among them, controlling the angle between the orientation direction of the orientation treatment and the wet film surface to be 0° to 45° can shorten the path length of the interlayer channel and improve the permeability of the polymer film. Further, the angle between the orientation direction of the orientation treatment and the wet film surface can be controlled to be 0° to 20°, 0° to 15°, 0° to 10° or 0° to 5°. Further, the angle between the orientation direction of the orientation treatment and the wet film surface can be directly controlled to be 0°, that is, the orientation direction of the orientation treatment is perpendicular to the surface normal direction of the wet film, and then the orientation treatment adopts parallel orientation, thereby making the interlayer channel perpendicular to the surface of the polymer film, fully improving the permeability of the polymer film.
[0030] In step S3, the precursor slurry is coated on the surface of the substrate and oriented. Specifically, the precursor slurry can be fed into the liquid separation chamber of the array coating die head through a feeding device in a constant temperature, constant humidity, dust-free environment, and an inert gas protection environment, and then transferred to the surface of the substrate, and the slurry is evenly coated with a scraper or a roller. Among them, the inert gas can be nitrogen, helium, etc.; the feeding device can be a gravity feeding device, a mechanical feeding device, a pneumatic feeding device, or a hydraulic feeding device; the slurry coating method can be a slit coating, a slope coating, or a curtain coating; the coating speed can be controlled at 3 mm / s to 20 mm / s.
[0031] In some embodiments of the present application, in step S3, the surface of the substrate is a hydrophobic surface; and / or the substrate is a porous substrate.
[0032] The surface of the substrate is a hydrophobic surface, which can induce the rearrangement of different components in the two-dimensional layered liquid crystal material in the coated precursor slurry through interfacial interaction, thereby promoting the transmembrane orientation of the interlayer channel. Specifically, long strips of amphiphilic liquid crystal molecules can be used, and their hydrophobic segments are longer than their hydrophilic segments, such as Figure 1 The amphiphilic liquid crystal shown in the figure, when the liquid crystal molecules are coated on a hydrophobic surface, the hydrophobic segments tend to stick to the hydrophobic surface, causing the molecules to "lie flat" on the hydrophobic surface, while the solvent layer that constructs the interlayer channel is a polar solvent, which repels the hydrophobic surface, and the solvent layer tends to be arranged perpendicular to the hydrophobic surface of the substrate, which is conducive to the transmembrane orientation arrangement of the interlayer channel, thereby constructing a uniformly sized, adjustable transmembrane oriented interlayer channel through hydrophilic and hydrophobic effects, molecular self-assembly behavior, and interfacial interactions.
[0033] The substrate may be a substrate made of a hydrophobic material, or a substrate with a hydrophobic surface treatment or modification. The substrate may be a metal material, an inorganic non-metal material, an organic material, or an organic-inorganic composite material.
[0034] The substrate may be a porous substrate, wherein the pore structure may be a through hole penetrating the substrate or a blind hole not penetrating the substrate, and the pore size may range from 1 μm to 1000 μm.
[0035] In the process of coating the precursor slurry on the substrate surface, the scraper or roller pressure, feed speed, and shear speed can be adjusted to adapt to slurries of different viscosities to generate a stress field suitable for the rotation, tumbling, and sliding of the two-dimensional liquid crystal, so as to induce the macroscopic orientation of the two-dimensional liquid crystal domains in the two-dimensional plane trans-membrane direction.
[0036] The coating thickness of the coating process can be controlled within a range of 5 μm to 300 μm, and the coating width can be controlled within a range of 0.01 m to 5 m.
[0037] In some embodiments of the present application, the relationship between the precursor slurry, substrate characteristics and coating process parameters can be controlled as shown in Table 1 below:
[0038] Table 1
[0039]
[0040] In some embodiments of the present application, in step S3, before the precursor slurry is coated on the surface of the substrate, the precursor slurry is first subjected to a defoaming treatment. The defoaming treatment may include sequentially performing microwave radiation and ultrasonic oscillation. Specifically, the precursor slurry may be subjected to microwave radiation and ultrasonic oscillation in sequence, and then the slurry is flowed into a container along a defoaming device with an inclined material guide surface, and then sealed with a sealing film and allowed to stand to eliminate the residual stress of the defoaming step. Among them, the precursor slurry may be first subjected to intermittent microwave heating to reduce the viscosity of the precursor slurry; the frequency of intermittent microwave heating may be controlled at 1 time / min to 120 times / min; the ratio of heating time to cooling time may range from 1:9 to 9:1. The precursor slurry is then subjected to ultrasonic oscillation to cause bubbles with smaller diameters in the precursor slurry to aggregate into bubbles with larger diameters under the action of sound pressure; the ultrasonic oscillation time may be controlled to be ≥10min. The precursor slurry is introduced into the container by a defoaming device with an inclined material guide surface. The precursor slurry flows along the inclined material guide surface, which can reduce the free rising distance and time of bubbles therein, so that the bubbles escape from the slurry surface under the action of buoyancy; wherein, the inclination angle θ of the inclined material guide surface or its tangent relative to the horizontal plane is 10°≤θ<90°, and the inclined material guide surface can be hemispherical or conical. Specifically, the defoaming device can adopt a bell cover surface, that is, the bell cover surface is used for defoaming. The standing time can be controlled to be ≥1 day. The above defoaming treatment can be carried out in a constant temperature, constant humidity and dust-free environment.
[0041] In some embodiments of the present application, in step S4, the in-situ polymerization curing treatment is any one of light treatment and heating treatment. For example, in an inert gas (such as nitrogen, argon, etc.) environment, the wet film is irradiated with light or heated to induce free radical polymerization to form a layered distribution of polymer chains to solidify the two-dimensional solvent channel; wherein, if the wet film contains a cross-linking agent, the mechanical strength can be improved by cross-linking adjacent polymer chain segments through the cross-linking agent.
[0042] Among them, if the in-situ polymerization curing treatment adopts light treatment, the initiator generally corresponds to a photoinitiator, for example, a vinyl-containing photoinitiator can be used. The light source of the light treatment can be a cold light source or a hot light source; the wavelength range can be controlled to be ≤450nm; and the light duration can be controlled to be 5s to 30min.
[0043] If the in-situ polymerization curing treatment adopts heating treatment, the initiator generally adopts a thermal initiator. The heating temperature can be controlled at 30 °C to 200 °C; the heating time can be 30 s to 60 min.
[0044] In some embodiments of the present application, the drying treatment is selected from at least one of hot air drying, microwave drying, convection drying, and infrared drying. In some embodiments, the drying treatment can be performed by sequentially performing hot air drying and microwave drying. Considering that hot air drying will preferentially dry the surface, which will cause uneven drying, during continuous drying, the oriented membrane channels may be destroyed when the water inside the membrane layer is discharged. Microwave radiation can dry more evenly, but its energy is relatively large, and long-term microwave radiation may also destroy the orientation of the channels between the membrane material layers. For this reason, hot air drying and microwave drying are combined. First, the area near the surface of the membrane layer is dried by hot air drying, and then microwave radiation drying with greater energy is used to dry, which is conducive to the effective drying of the inside of the membrane layer. The combination of the two drying methods can effectively maintain the channel structure between the membrane material layers.
[0045] Hot air drying can be specifically assisted by a baffle with several ventilation holes. The ventilation holes on the baffle are evenly arranged, and the hot air is blown to the film layer obtained by in-situ polymerization and curing through the ventilation holes on the baffle. Among them, the shape of the ventilation holes on the baffle is not limited, and can be circular, rectangular, square, elliptical, etc.; the hot air temperature can be controlled at 40 ° C ~ 85 ° C; the air supply speed can be controlled at 0.01 m / s ~ 50 m / s. The use of a baffle with several ventilation holes to assist hot air drying can further help avoid destroying the orientation of the film during the drying process. After completing the hot air drying, microwave radiation is further performed to strengthen the film structure; the processing frequency of microwave radiation can be controlled at 1 time / min ~ 120 times / min.
[0046] In some embodiments of the present application, in step S4, after the drying process is completed, a film stripping process is also included. Before the stripping process, the polymer film is loaded on the surface of the substrate. The stripping process can be specifically performed by stripping the polymer film from the substrate with the aid of a stripping device. The stripping device can use a wedge-shaped stripping piece. The stripping process can specifically control the angle between the force direction of the wedge-shaped stripping piece and the substrate surface (or the stripping entry angle) to be 0° to 45°; in addition, in combination with the structural characteristics of the polymer film, in order to facilitate the complete and continuous stripping of the polymer film, the hardness of the wedge-shaped stripping piece can be designed to be HRC>40 and the surface roughness <1 μm.
[0047] In some embodiments of the present application, in step S4, after the drying process is completed, a membrane loading process is further included, specifically, the membrane loading process is used to enhance the bonding strength between the membrane layer and the substrate, ensure the close bonding between the two, and form a stable membrane loading structure. The membrane loading process may be a hot pressing process, a chemical bonding process, a physical electrostatic adsorption process, etc.
[0048] In a second aspect of the present application, a polymer membrane is provided, which is prepared by the above-mentioned method for preparing a polymer membrane. The polymer membrane has a plurality of two-dimensional channels oriented across the membrane, that is, the extension direction of the two-dimensional channels intersects with the surface extension direction of the polymer membrane and penetrates the polymer membrane. The two-dimensional channels in the polymer membrane have uniform size and have high selectivity and high permeability.
[0049] In some embodiments of the present application, the extension direction of the two-dimensional channel is perpendicular to the surface of the polymer film.
[0050] In some embodiments of the present application, the two-dimensional channel is generally a two-dimensional laminar channel.
[0051] In some embodiments of the present application, the size of the two-dimensional channel is distributed in the sub-nanometer and nanometer ranges. Specifically, the size of the two-dimensional channel can be controlled to be between 0.1 nm and 10 nm.
[0052] In some embodiments of the present application, the angle between the extension direction of the two-dimensional channel and the surface normal of the polymer film is 0° to 45°, that is, the angle between the two-dimensional channel and the surface of the polymer film is 45° to 90°.
[0053] The third aspect of the present application is to propose a method for preparing the aforementioned polymer membrane or the application of the aforementioned polymer membrane in membrane separation. The aforementioned method for preparing the polymer membrane is a method for preparing a polymer membrane with controllable interlayer channels. In the membrane separation application process, the size of the interlayer channels of the polymer membrane can be precisely controlled according to the separation requirements, so that the prepared polymer membrane can meet the separation requirements. BRIEF DESCRIPTION OF THE DRAWINGS
[0054] The present application is further described below with reference to the accompanying drawings and embodiments, wherein:
[0055] Figure 1 It is an amphiphilic liquid crystal that can be used in the method for preparing the polymer film of the present application;
[0056] Figure 2 The process flow diagram of the method for preparing the polymer film of Example 1 is shown;
[0057] Figure 3 Schematic diagram of material transformation in the polymer film preparation process of Example 1;
[0058] Figure 4 This is a physical picture of the precursor slurry in Example 1;
[0059] Figure 5 This is a physical comparison diagram of the precursor slurry before and after defoaming in Example 1;
[0060] Figure 6 The polarized microtexture image of the precursor slurry before and after degassing in Example 1;
[0061] Figure 7 This is the polarized microtexture image of the film layer before and after photocuring in Example 1;
[0062] Figure 8 This is a physical picture of the polymer film obtained in Example 1;
[0063] Fig. 9 This is a surface scanning electron micrograph of the polymer film obtained in Example 1;
[0064] Fig.10 The cross-sectional electron microscope image and transmission electron microscope image of the polymer film obtained in Example 1;
[0065] Fig.11 This is a schematic diagram of the process flow of the method for preparing the polymer film of Example 5;
[0066] Fig.12 This is the polarized microtexture image of the polymer film obtained in Comparative Example 1. DETAILED DESCRIPTION
[0067] The following will clearly and completely describe the concept of the present application and the technical effects produced in combination with the embodiments, so as to fully understand the purpose, features and effects of the present application. Obviously, the described embodiments are only part of the embodiments of the present application, not all of them. Based on the embodiments of the present application, other embodiments obtained by those skilled in the art without creative work are all within the scope of protection of the present application.
[0068] Example 1
[0069] A method for preparing a polymer film, see Figure 2 and Figure 3 , the preparation method comprises the following steps:
[0070] S1. A two-dimensional lamellar liquid crystal system with a polar solvent content of 1 wt% is prepared by mixing 99 wt% of an amphiphilic liquid crystal and 1 wt% of a polar solvent; wherein the polar solvent is water, and the amphiphilic liquid crystal is tetradecylvinyl imidazole hydrogen sulfate, and its structural formula is:
[0071] .
[0072] Specifically, a solid powder of tetradecyl vinyl imidazole hydrogen sulfate is placed in a centrifuge tube, and water is added drop by drop to prepare a two-dimensional liquid crystal solid-liquid mixture with a solvent content within the liquid crystal phase range; the solid-liquid mixture is placed in a refrigerator and frozen until completely solidified; the mixture is then taken out and thawed at room temperature of 25°C, and gently stirred with a thin glass rod; the above freezing, thawing and stirring steps are repeated 10 times in sequence; a centrifuge is used to rotate at 500 r / min and centrifuge at room temperature for 30 min to remove bubbles generated by stirring in the system; a sealing film is used to seal the mouth of the centrifuge tube to prevent solvent volatilization and impurities from mixing in, and the tube is allowed to stand for 1 day to achieve sufficient and uniform self-assembly of tetradecyl vinyl imidazole hydrogen sulfate molecules in water, while eliminating the residual stress generated between domains during the stirring and mixing process of the sample, to obtain a two-dimensional layered liquid crystal system, and its texture characteristics are detected using a polarizing microscopy imaging system, and a uniform "focal cone texture" characteristic texture is observed, proving the existence of a layered phase.
[0073] S2. Preparing a precursor slurry by mixing an additive consisting of a thermal initiator and a crosslinking agent with a two-dimensional lamellar liquid crystal system. Ethylene glycol dimethacrylate is used as a crosslinking agent, ammonium persulfate is used as a thermal initiator, the mass ratio of the crosslinking agent to the thermal initiator is 1:1, and the mass ratio of the additive to the two-dimensional lamellar liquid crystal system is 6:94.
[0074] Specifically, ethylene glycol dimethacrylate is used as a crosslinking agent and ammonium persulfate is used as a thermal initiator. The material is taken according to the mass ratio of the crosslinking agent to the thermal initiator of 1:1, dissolved in dichloromethane, and fully stirred for 10 minutes with a glass rod. The solvent is removed by vacuum rotary evaporation and placed in a negative pressure environment for not less than 8 hours to obtain a fully mixed additive. Then, according to the mass ratio of the additive to the two-dimensional lamellar liquid crystal system of 6:94, the additive is added to the two-dimensional liquid crystal system prepared in step S1. Use an inert metal rod to fully stir so that the solid and liquid phases are initially mixed evenly; use ultrasonic vibration to vibrate at room temperature for 60 minutes to fully dissolve the undissolved solids in the system; then repeat the above stirring and mixing and ultrasonic vibration steps 4 times in sequence; use a centrifuge at a speed of 2000r / min and centrifuge at room temperature for 5 minutes to remove the upper slurry with a high bubble content, and repeat the above steps 3 times to remove the larger bubbles generated in the system due to stirring; the membrane-sealed centrifuge tube is left to stand for 1 week to eliminate residual stress, and a precursor slurry is obtained, the viscosity of which is 6×10 8 mPa·s; the texture characteristics were detected using a polarizing microscopy imaging system, and a uniform "focal cone texture" characteristic texture was observed, proving the existence of a lamellar phase.
[0075] S3, defoaming the precursor slurry.
[0076] Specifically, in a dust-free operating room at a humidity of 95 RH%, a temperature of 25°C, the precursor slurry was intermittently heated by a microwave chemical reactor, 5 times per minute, each heating for 5 s, and then cooled for 7 s; the heating temperature was set at 55°C to 60°C. Then, an ultrasonic cell disruptor was used at a power of 1 W / cm 2 The precursor slurry was subjected to ultrasonic vibration. The treated precursor slurry flowed along the interface of a hemispherical bell jar surface with a diameter of 30 cm, wherein the tangent of the hemispherical bell jar surface was inclined at an angle of 45° relative to the plane; the treated slurry was placed in a beaker, sealed with a membrane and left to stand for 1 week to obtain a bubble-free precursor slurry, such as Figure 4 As shown in FIG. 1 , the actual comparison and polarized microtexture diagram of the precursor slurry before and after the defoaming treatment in step S3 are respectively as shown in FIG. Figure 5 , Figure 6 As shown, Figure 6 Here P and A represent the polarizing direction and analyzing direction of the polarizing microscope respectively.
[0077] S4, coating the precursor slurry on the surface of the substrate and performing parallel alignment treatment to obtain a wet film.
[0078] Specifically, in a dust-free operating room with a humidity of 95 RH% and a temperature of 25°C, the precursor slurry was injected into the liquid separation chamber of the array coating die head through a gear pump under nitrogen protection, and slit coating was used to uniformly transfer and coat the slurry onto the PMMA substrate transported on the conveyor belt at a coating speed of 3 cm / s. The conveyor belt speed was 3 cm / s, the coating width was 10 cm, and the thickness was 10 μm. A metal scraper was used to apply horizontal shear force to the coating slurry. The scraper contact surface was flat, the cutting angle was 30°, the departure angle was 200°, the shear force was 100 N, and the mechanical friction force was parallel oriented during the coating process. After coating, a wet film was formed on the substrate surface.
[0079] S5. Performing in-situ polymerization curing and drying treatment on the wet film.
[0080] In a dust-free operating room at a humidity of 95 RH%, a temperature of 25°C, a uniform thickness solution film is heated to 90°C and maintained for 15 min to 45 min, so that the vinyl forms a layered distribution of polymer chains through thermal polymerization; ethylene glycol dimethacrylate cross-links adjacent polyethylene layers to provide mechanical strength, converting the uniform thickness solution film into a solid wet film, wherein the polarized microtexture of the film layer before and after in-situ polymerization and curing treatment is shown in FIG. Figure 7 As shown, Figure 7 Here P and A represent the polarizing direction and analyzing direction of the polarizing microscope respectively.
[0081] After the above in-situ polymerization curing treatment is completed, a rectangular slit with a size of 5 cm × 10 cm and a spacing of 5 cm is arranged in an array, and hot air is blown at a vertical angle to the solid wet film after in-situ curing. The hot air temperature is 60°C and the wind speed is 0.5 m / s for 5 minutes. The solid wet film is intermittently heated by a microwave chemical reactor, each time for 5 minutes, and then cooled for 2 minutes. The radiation intensity is 700 mW / cm 2 , to complete the drying of the solid wet film.
[0082] S6, film stripping, that is, stripping the film material from the substrate surface. Specifically, a metal wedge-shaped stripping piece can be used to apply a horizontal shear force to the polymer film to achieve the stripping of the film from the substrate. The cutting angle of the wedge-shaped stripping piece can be 3°, and the shear force is 25 N. After the stripping is completed, the finished polymer film is obtained through a winding process, such as Figure 8 shown.
[0083] Example 2
[0084] The difference between this embodiment and embodiment 1 is that the raw material ratio of the two-dimensional lamellar liquid crystal system in step S1 is: 80 wt % amphiphilic liquid crystal and 20 wt % polar solvent, and the content of polar solvent in the two-dimensional lamellar liquid crystal system is 20 wt %; the precursor slurry prepared in step S2 is 4×10 6 mPa·s; other operations were the same as in Example 1 to obtain a polymer membrane.
[0085] Example 3
[0086] The difference between this embodiment and embodiment 1 is that the raw material ratio of the two-dimensional lamellar liquid crystal system in step S1 is: 60wt% amphiphilic liquid crystal and 40wt% polar solvent, and the content of polar solvent in the two-dimensional lamellar liquid crystal system is 40wt%; the precursor slurry prepared in step S2 is 5×10 5 mPa·s; other operations were the same as in Example 1 to obtain a polymer membrane.
[0087] The thickness of the polymer film prepared in this embodiment is about 10 μm. The surface scanning electron microscope image of the polymer film is as follows Fig. 9 As shown, Fig. 9 The left side of the figure shows the surface electron microscope image of the polymer film, and the right side shows the local simulation image of the polymer film. Fig. 9 It can be seen that the polymer membrane prepared above retains two-dimensional channels with uniform size and distribution vertically oriented along the transmembrane direction. The channels are arranged anisotropically in the membrane surface direction and arranged vertically to the membrane surface in the transmembrane direction. The cross-sectional electron microscopy and projection electron microscopy images of the polymer membrane are shown in Figure 2. Fig.10 As shown, Fig.10 (a) is an electron microscope image; (b) is a projection electron microscope image. Fig.10 It can be seen that the cross-section of the polymer film has a two-dimensional layered structure with vertical orientation, uniform size and distinct morphological characteristics, in which two-dimensional vertical channels with uniform size and sub-nanometer or nanometer size are periodically distributed. According to theoretical calculations, the channel width is 0.9nm.
[0088] Example 4
[0089] The difference between this embodiment and embodiment 1 is that the raw material ratio of the two-dimensional lamellar liquid crystal system in step S1 is: 50wt% amphiphilic liquid crystal and 50wt% polar solvent, and the content of polar solvent in the two-dimensional lamellar liquid crystal system is 50wt%; the precursor slurry prepared in step S2 is 4×10 4 mPa·s; other operations were the same as in Example 1 to obtain a polymer membrane.
[0090] Example 5
[0091] The preparation method of the polymer film of this embodiment is as follows Fig.11 As shown, the difference from Example 1 is that the film stripping operation in step S6 is cancelled, and the finished polymer film is obtained through a winding process after completing step S5, and the other operations are the same as those in Example 1.
[0092] The above polymer film is composed of a substrate and a film layer loaded on the surface of the substrate. In order to improve the bonding strength between the substrate and the film layer, the film loading treatment, such as heat pressing treatment, chemical bonding treatment, physical electrostatic adsorption treatment, etc., can be performed before winding.
[0093] Polymer membrane performance testing
[0094] Water flux: The water flux of the polymer membrane was tested using a pressure-driven dead-end filter cup. Deionized water was used as the test solvent. The polymer membrane was first immersed in deionized water for pre-wetting treatment for 1 hour. The pressure during the test was set to 5 bar, and the effective membrane area of the test device was 100 cm 2 ; The water flux calculation formula is as follows:
[0095] ;
[0096] in, J is the water flux, in Lm -2 h -1 ; Q is the volume of deionized water passing through, the unit is L; A is the effective membrane area, in m 2 ; Δt is the test time, the unit is h.
[0097] Li + / Mg 2+Ion separation ratio: Prepare MgCl2 solution and LiCl solution with a concentration of 1000ppm respectively, and use an ultrafiltration cup with a stirring tank to evaluate the ion separation performance of the polymer membrane by dead-end filtration. Use a nitrogen bottle to connect the upstream of the ultrafiltration cup to provide a constant pressure, and the effective area of the membrane is 4cm 2 . Take 1000ppm MgCl2 solution as stock solution, collect the filtrate downstream of the membrane under 5bar working condition, use conductivity meter to test the conductivity of stock solution and filtrate, calculate the MgCl2 concentration in the filtrate with reference to the standard curve, 1-(filtrate concentration / stock solution concentration) = ion retention rate; measure the retention rate of LiCl in the same way; repeat the above test for no less than 3 times and take the average value; Li + / Mg 2+ Ion separation ratio = Mg retention rate / Li retention rate, which is used to obtain the ion separation performance of the membrane.
[0098] The above method was used to test the properties of the polymer films prepared in Examples 1 to 4. The results are shown in Table 2 below.
[0099] Table 2
[0100]
[0101] The hydration kinetic diameters of Li ions and Mg ions are approximately 0.7nm and 0.8nm, respectively, with a difference of 0.1nm. The difference in pore size leads to different resistances to the two ions when they pass through the channel. Mg ions with larger diameters encounter greater resistance and are therefore more difficult to pass through the channel. Therefore, the key to achieving magnesium-lithium separation is to control the channel size. Combined with Table 2, it can be seen that the channel in the membrane can be specifically controlled to 0.6 nm to 1nm. In order to effectively achieve magnesium-lithium separation, it is preferred to use a polymer membrane prepared by the preparation method of Examples 3 and 4 with both high water flux and lithium-magnesium ion separation ratio (or selectivity). The specific selection can be made according to the separation process parameter requirements. For example, if Li + / Mg 2+ The ion separation ratio is required to be not less than 12 or 13, and the polymer membrane prepared by the preparation method of Examples 3 and 4 can be selected; if Li + / Mg 2+ If the ion separation ratio is required to be no less than 14, the polymer membrane prepared by the preparation method of Example 3 can be selected.
[0102] In addition, during the research process, the inventors conducted research experiments on the effect of further increasing the amount of polar solvent on the polymer film structure. The study found that when the polar solvent content of the two-dimensional lamellar liquid crystal system exceeds 80wt%, the aforementioned two-dimensional lamellar channels are not formed in the polymer film.
[0103] For example, based on Example 1, the inventors changed the raw material ratio of the two-dimensional lamellar liquid crystal system in step S1 to: 15 wt % amphiphilic liquid crystal and 85 wt % polar solvent, and the other operations were the same as in Example 1 to prepare a polymer film according to this method. The polarizing microscope image of the polymer film is shown in FIG. Fig.12 As shown, Fig.12 P and A represent the polarization direction and analysis direction of the polarizing microscope respectively. Fig.12 The polarized light microtexture image shown is completely dark, and no two-dimensional layer channels appear in the polymer film.
[0104] From the above, the polymer membrane prepared in the above embodiments has a number of two-dimensional lamellar channels with uniform transmembrane orientation, size and distribution, and the preparation method of the above polymer membrane can control the size of the two-dimensional lamellar channels between polymer membrane layers by controlling the amount of polar solvent added within a specific range or controlling the polar solvent content in the two-dimensional lamellar liquid crystal system, so as to achieve uniform and controllable size of the channels between membrane layers and continuous adjustable size at the nanometer or sub-nanometer scale. The prepared polymer membrane has both high selectivity and high permeability. The above polymer membrane and its preparation method can be applied to the field of membrane separation. Specifically, according to the separation requirements, the size of the channels between the polymer membrane layers can be precisely controlled by controlling the amount of polar solvent added, so that the obtained polymer membrane meets the membrane separation requirements.
[0105] The above-mentioned embodiments only express several implementation methods of the present application, and the descriptions thereof are relatively specific and detailed, but they cannot be understood as limiting the scope of the present application. It should be pointed out that, for ordinary technicians in this field, several variations and improvements can be made without departing from the concept of the present application, and these all belong to the protection scope of the present application.
Claims
1. A method for preparing a polymer film, characterized in that: The following steps are involved: S1. A two-dimensional lamellar liquid crystal system is prepared by mixing an amphiphilic liquid crystal with a polar solvent; the content of the polar solvent in the two-dimensional lamellar liquid crystal system is 1wt% to 80wt%; the amphiphilic liquid crystal is a long strip of amphiphilic liquid crystal molecules having a hydrophilic segment and a hydrophobic segment, and the hydrophobic segment is longer than the hydrophilic segment; the long strip of amphiphilic liquid crystal molecules is selected from any one of the amphiphilic liquid crystals of the following structural formulas: In the groups A and A', n>8, and in the group D', R1 is selected from alkylene; S2, mixing an additive including an initiator with the two-dimensional lamellar liquid crystal system to prepare a precursor slurry; S3, coating the precursor slurry on the surface of the substrate and performing an orientation treatment to obtain a wet film; The orientation direction of the orientation treatment intersects with the surface normal direction of the wet film; the surface of the substrate is a hydrophobic surface; S4, performing in-situ polymerization curing and drying treatment on the wet film.
2. The method for preparing a polymer film according to claim 1, characterized in that: In step S2, the mass ratio of the additive to the two-dimensional lamellar liquid crystal system is 1:(1-100000); and / or the viscosity of the precursor slurry is 1×10 3 mPa·s~1×10 9 mPa·s.
3. The method for preparing a polymer film according to claim 2, characterized in that: The two-dimensional lamellar liquid crystal system and the amphiphilic liquid crystal in the precursor slurry form a focal conic texture; And / or, the additives include 0-99 wt % of functional monomers, 0-99 wt % of cross-linking agents, 1-100 wt % of initiators, and 0-99 wt % of thermal inhibitors.
4. The method for preparing a polymer film according to claim 1, characterized in that: In step S2, the additive is first placed in an organic solvent for blending, and then the organic solvent is removed, and then mixed with the two-dimensional lamellar liquid crystal system to prepare a precursor slurry; And / or, the mixing of the additive with the two-dimensional lamellar liquid crystal system comprises: first stirring and mixing, and then ultrasonically oscillating; and then sequentially repeating the stirring and mixing and the ultrasonic oscillating for more than two times.
5. The method for preparing a polymer film according to claim 1, characterized in that: In step S1, the mixing method of the amphiphilic liquid crystal and the polar solvent is selected from at least one of a stirring ultrasonic method, a freeze-thaw cycle method, and a rotary evaporation method.
6. The method for preparing a polymer film according to claim 1, characterized in that: In step S3, the angle between the orientation direction of the orientation treatment and the surface of the wet film is 0° to 45°; and / or, the orientation treatment is performed by mechanical friction during the coating process.
7. The method for preparing a polymer film according to claim 1, characterized in that: In step S3, the substrate is a porous substrate.
8. The method for preparing a polymer film according to any one of claims 1 to 7, characterized in that: In step S4, the in-situ polymerization curing treatment is any one of light treatment and heating treatment; and / or the drying treatment is selected from at least one of hot air drying, microwave drying and infrared drying.
9. A polymer film, characterized in that The polymer film is prepared by the method for preparing the polymer film according to any one of claims 1 to 8.
10. Use of the polymer membrane obtained by the method for preparing the polymer membrane according to any one of claims 1 to 8 or the polymer membrane according to claim 9 in membrane separation.
Citation Information
Patent Citations
Liquid crystal slurry, ion transmission composite membrane and solid-state battery
CN118725875A